Metacarpal bone Ewing's sarcoma : utilizing autologous metatarsal graft as a reconstruction option following resection - Wan Ismail, Wan Faisham Numan; Sharifudin, Mohd Ariff; Krishnan, Jagdish; Wan, Zulmi; Mat Zin, Nor Azman; Mohamed Amir, Nawaz Hussain (2013)
Introduction: Ewing’s sarcoma is a rare, malignant neoplasm; common in both the axial and appendicular skeleton but originates rarely in the bones of the hand. Historically, treatment involves combination of chemotherapy and radiotherapy. Depending on the anatomic location, the role of surgical intervention remains limited.